Health policies from a gender perspective: An approach from the exam of tobacco control plans - Jiménez Rodrigo, María Luisa (Investigaciones Feministas (Feminist Research), 2015)
Although research on gender biases in health policies is extensive, tobacco control policies, spite of smoking feminization processes, have been scarcely examined in Spain from a critical gender lens. This paper focuses on the analysis of gender and intersectional biases that could affect the design of tobacco control plans as have been developed at national and regional levels. Even though sexsegregated data is mandatorily incorporated in the majority of plans, women specific characteristics remain invisible in the setting of objectives and interventions with the exception of pregnancy. Consequently, there is not drawing of distinct profiles that take into account gender intersection with other inequality axes.